Linguistic justice international law and language policy - Mowbray, Jacqueline (Oxford : Oxford University Press, 2013)
An investigation into international law and language policy this text uses critical analysis to conduct an examination of the aspects of international law which affect language use.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Language and languages -- Law and legislation